National hydroelectric power resources study. Preliminary inventory of hydropower resources. Volume 6. Northeast region (Institute for Water Resources (Army), Fort Belvoir, VA (USA), 1979)
In the Northeast region, the physical potential for all sites exceeds 33,000 MW of capacity with an estimated average annual energy of some 153,000 GWH. By comparison, the available data represent about 6% of the total capacity and 11% of the hydroelectric energy potential estimated for the entire US. Of the total capacity estimated for the region, 6100 MW has been installed. The remainder (27,200 MW, excluding the undeveloped capacity in the New England States) is the maximum which could be developed by upgrading and expanding existing projects (18,700 MW), and by installing new hydroelectric power capacity at all potentially feasible, undeveloped sites (8500 MW). Small-scale facilities account for about 15% of the region's total installed capacity, but another 1800 MW could be added to these and other small water-resource projects. In addition, 500 MW could be installed at potentially feasible, undeveloped small-scale sites. The small-scale resource varies considerably, with the states of New York, Maine, and New Hampshire having the largest potential for incremental development at existing projects in the Northeast region. West Virginia, Maryland, Delaware, New Jersey, Pennsylvania, New York, Connecticut, Massachusetts, Rhode Island, New Hampshire, Vermont, and Maine comprise the Northeast region.